RANCANG BANGUN LIFT BARANG 3 LANTAI BERBASIS PLC DENGAN DETEKSI KELEBIHAN BEBAN - Lestari, Sri Wahyu Puji; Damayanti, Eva (Jurnal TEDC; Vol 19 No 1 (2025): JURNAL TEDC, 2025)
This study examines the design and evaluation of a three-story freight elevator system equipped with a weight sensor to enhance load measurement accuracy and operational efficiency. The designed system integrates a load cell and a DC motor, with tests conducted on load variations (200 g, 500 g, 700 g, and 1000 g) to assess load measurement accuracy and motor performance. The test results indicate that the placement of the load cell at the corner and middle side positions of the cabin causes significant measurement deviations, with deviations of up to -0.087% on the average total load. Additionally, a decrease in lifting speed and an increase in DC motor power consumption were observed with increasing load. This study aims to evaluate various aspects of the system design, the accuracy of load cell-based measurements, and the effect of mass variations on DC motor performance. Further research is recommended to explore testing under various environmental conditions and on a larger scale such as industrial loads to improve the accuracy and efficiency of the elevator system.